(3LGeY GdHjGf Yf JChjd Ci GdaQbGfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3hChd eG ajg Gdbhd ai JChjd bhdg Ld KfGDg (B" (3bGdJ CfG jchf di ZdGe hde jeSSfi HTQ (B" (3jbhd JYGdi PcQg bGdJ eQje dLHQjd CfG jchf di ZdGe s
(3BNQgG (B:s
(3jfJgi HBNQ ShQI Wg Hbhdg ceG bGd KfGAg djYde Ci GdMRHjf CMUi hGdfUH Ydi EYeGd JYdehf ajgG ceG bGd Ld KfGDg hGddg jYde GdeaSO ef GdeUdM s
(3bWYI ai JaSjQ BjGJ ef ShQI eQje hWgs
(3fSNI Ydi Qb ZRGds
(3ef JMHjS GdSdWGf CHj YHO Gddg GdefJUQ GdeQjfi SfI (B5827s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs